The business of fashion children's wear industry [videorecording] - Diamond, Jay; Diamond, Ellen (The Business of fashion, 1990)
Explains the creation and marketing of children's clothing. Discusses various aspects of the clothing industry, including fashion forecasting, design and production, fashion promotion, and selling the line.